Mobility after job loss in Germany: the effects of regional economic opportunities and economic worries on mobility intentions and behaviour - Katrin Rickmeier (Review of Regional Research, 2025)
This study examines the impact of local economic opportunity structures on mobility intentions and mobility behaviour subsequent to involuntary job loss in Germany. Previous research has demonstrated that job loss leads to an increased propensity for regional mobility; however, the role of the regional economy as a~push factor and its influence on the decision to relocate remains unclear. The focus of the study at hand is on the opportunities provided by locational factors and an examination of the broader context in which regional mobility after job loss occurs. Logistic regression models are set up using data from the German Socio-Economic Panel study, which is complemented by a~unique combination of spatial structure indicators. The results demonstrate that job loss has no effect on the mobility intentions of displaced workers. However, it increases the propensity to relocate within Germany. Furthermore, a~favourable economic situation in the home region makes mobility intentions of displaced workers less likely. This is indicated by a~negative effect of the local GDP and a~positive effect of the occupation-specific local unemployment rate. A~mediation analysis does not confirm a~hypothesised omitted variable bias of economic worries in the effect of regional economic characteristics on the mobility intentions of displaced workers.
Keywords: J61; J64; R12; R23; 910; Internal migration; Job loss; Regional opportunity structures; Unemployment